Estudo metabolômico e atividade gastroprotetora de macela-da-terra (Egletes viscosa L.-Asteraceae) - Carvalho, Kaline Rodrigues (2021)
Egletes viscosa Less (Asteraceae) is an herb popularly known as “macela-da-terra” in the Northeast of Brazil, where its flower buds (FB) are used in the form of tea/infusion for gastrointestinal disorders. Indeed, its gastroprotective properties have been attributed to the flavonoid ternatine, and to the diterpenes tanabalin and centipedic acid. Such plant has two chemical varieties based on the chemical composition of the essential oil: chemotype A, which is rich in trans-pinocarveyl acetate and cis-isopinocarveyl acetate-rich chemotype B. As a result, the present study aimed to perform a metabolomic study and evaluate the gastroprotective activity of FB and leaves of the two chemotypes of E. viscosa. The plant materials investigated were of wild origin, cultivated by sowing or purchased commercially, then they were prepared in different forms and analyzed by chromatographic and/or spectrometric techniques: gas chromatography coupled to mass spectrometry (GC-MS), near infrared spectroscopy (NIR), hydrogen nuclear magnetic resonance (1H NMR) and ultra-efficiency liquid chromatography coupled to mass spectrometry (UPLC-MS). Next, the generated data were combined with chemometrics for the discrimination of chemotypes. The GC-MS analyses were applied to FB extracted by hydrodistillation and by solid phase microextraction (SPME), which had its extraction conditions previously optimized through a central rotational composite design. The best conditions were achieved with FB extracted with DVB / CAR / PDMS fiber for 6.6 min at 40 ºC. The SPME method has the advantages of being non-destructive and requiring an amount of FB 300x lesser than the hydrodistillation. The NIR method also discriminated the chemotypes in a non-destructive way using a portable device, which can be applied in situ (eg. farms). In addition, UPLC-MS and 1H NMR methods were developed and validated for the quantification of the compounds, revealing that the FB from the chemotype A presents higher contents of the three active principles. All analytical methods showed to be simple, fast, reliable and complementary for authenticity and / or quality control of E. viscosa raw materials and products. In addition, the UPLC-MS analysis allowed the identification of 36 compounds in the infusions (FB: 25, leaves: 20), 20 of them have been reported for the first time in the species, including derivatives of caffeic acid, flavonoids and diterpenes. Chemometric analysis of the UPLC-MS data indicated that chemotypes A and B also showed differences in the concentrations of many non-volatile constituents. The gastroprotective activity of FB and leaves was evaluated through ethanol-induced gastric lesions in mice. All samples exhibited a gastroprotective effect (50 - 400 mg.kg-1) and were devoid of toxicity. FB were more potent than leaves, showing gastroprotection at doses of 50 mg.kg-1. There was no significant difference between tea and tincture samples. The chemotypes showed only small differences in the mechanism of action, which involves antioxidant, NO, prostaglandins, K + channels and TRPV1 receptors. Our study is the first report proving the gastroprotective effect of E. viscosa in the pharmaceutical forms consumed by the population.